2019
DOI: 10.7235/hort.20190033
|View full text |Cite
|
Sign up to set email alerts
|

Growth Promotion Effects of Plant Extracts on Various Leafy Vegetable Crops

Abstract: Though the mechanisms are not yet fully understood, the macro-and micro-nutrients, amino acids, and hormone-like growth substances present in plants (whole plants and their extracts) may lead to biostimulatory activities when applied to crops. This study was conducted to determine the growth promotion effects on lettuce (Lactuca sativa L.) of plant extracts obtained by different extraction methods (water, boiling water, fermentation, and ethanol) from 31 agricultural materials. We also determined the growth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This can be explained by the growth regulators present in the plant extracts that improved the growth variables (Silva et al, 2008;Ijato et al, 2010). Jang and Kuk (2019) reported that plant extracts hade growth promotion effects on various crops, which was corroborated by the current results. The same outcomes resulted with extract from Tephrosia vogelii and Tithonia diversifolia applied as foliar sprays on beans at a concentration of 10% weight per volume, which increased the chlorophyll content, the number of pods per plant bean and the overall seed yield (Mkindi et al, 2020).…”
Section: Bioactivity Of Plant Extracts On Rice Growth Brown Spot and ...supporting
confidence: 91%
“…This can be explained by the growth regulators present in the plant extracts that improved the growth variables (Silva et al, 2008;Ijato et al, 2010). Jang and Kuk (2019) reported that plant extracts hade growth promotion effects on various crops, which was corroborated by the current results. The same outcomes resulted with extract from Tephrosia vogelii and Tithonia diversifolia applied as foliar sprays on beans at a concentration of 10% weight per volume, which increased the chlorophyll content, the number of pods per plant bean and the overall seed yield (Mkindi et al, 2020).…”
Section: Bioactivity Of Plant Extracts On Rice Growth Brown Spot and ...supporting
confidence: 91%
“…In the present investigation, different concentrations of A. saligna FAE had a significant impact on biochemical compounds (antioxidant, flavonoid, total phenolic, and carbohydrates) and total soluble content. In this sense, using biostimulants raised the biochemical components of a variety of leafy vegetables while improving their quality 39 , 96 , 97 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, a growing interest in the application of plant extracts as an alternative to the agrochemicals employment at cropping systems has become a reality (CARMELLO & CARDOSO, 2018;JANG & KUK, 2019;THUERIG et al, 2018;NARASIMHAMURTHY et al, 2019), hence, studies that aim the characterization of the existing compounds in plant extracts used in agriculture, including seed treatment.…”
Section: Introductionmentioning
confidence: 99%